2021
DOI: 10.1186/s12913-021-06119-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for using technology in communication about symptoms post hospital discharge

Abstract: Background Technology is increasingly transforming the way we interact with others and undertake activities in our daily lives. The healthcare setting has, however, not yet realised the potential of technology solutions to facilitate communication between patients and healthcare providers. While the procedural and policy requirements of healthcare systems will ultimately drive such solutions, understanding the preferences and attitudes of patients is essential to ensure that technology implemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…There was no consensus on the ideal mode of communication, and patient preferences regarding interaction also differed. A diversity in patient preferences regarding technology to manage health and communicate with health professionals has been observed before (Alexander et al, 2021). Another important determinant for the experienced value of RPM, was how TM teams met the expectations and information needs of patients toward the system, how patients were involved in the decision of starting RPM.…”
Section: Discussionmentioning
confidence: 78%
“…There was no consensus on the ideal mode of communication, and patient preferences regarding interaction also differed. A diversity in patient preferences regarding technology to manage health and communicate with health professionals has been observed before (Alexander et al, 2021). Another important determinant for the experienced value of RPM, was how TM teams met the expectations and information needs of patients toward the system, how patients were involved in the decision of starting RPM.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have sought to incorporate patient input around specific features associated with digital health technologies across disease areas, [58][59][60][61] suggesting that patients prefer digital health technologies primarily for its convenience and communication. 62,63 In the SMI space, a recent qualitative study of patients with SMI, found that with respect to digital health tools, data privacy is a major concern for patients with SMI. 64 Additional work should be conducted to capture the perspectives of and preferences for features and attributes of digital health technologies among patients diagnosed with SMI.…”
Section: Discussionmentioning
confidence: 99%
“…There may be shared learnings, that can be useful in future implementations of text-based communication following discharge. Some studies focus on patients' and healthcare professionals' perceptions and preferences [24][25][26][27][28] and others on organisational factors that affect acceptance and diffusion of text-based communication. 22 23 Husain et al 22 implemented and evaluated a web-based clinical communication system for team-based care with patients with a focus on facilitators and barriers, but found that even though the system could fill a gap of communication, existing modes of communication, workflows, incentives and lack of integration with electronic medical records were barriers to adoption.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%